Pengaruh Keterlibatan Orang Tua terhadap Kesiapan Belajar pada Anak di TK Al-Amien Jember - Aminah, Aminah; Ervina, Iin; Sari, Anggraeni Swastika (Jurnal Parenting dan Anak, 2023)
Parents have a crucial role in nurturing, supporting, and educating their children. In reality, Retnaningtya & Pararamitha (2015) found that most parents only make minimal efforts to control and educate their children's development, with very few being significantly involved in their children's education. The aim of this research is to determine the influence of parental involvement on children's readiness to learn at TK Al-Amien Jember. This research employs a descriptive quantitative method. The total population is 271, with 142 parents as the sample, representing all the students at TK Al-Amien Jember. The sampling technique used is simple random sampling. Data collection utilizes two scales adapted and modified from the parental involvement scale by Hoover-Dempsey and Sandler (2005), consisting of 21 items, and the readiness to learn scale by Slameto (2010), consisting of 20 items. The analysis method involves testing the measurement tool, assumptions, and hypotheses using SPSS for Windows version 21 and MS Excel 2010. The correlation coefficient results indicate a 0.275 correlation between parental involvement and readiness to learn, with a two-tailed Sig value of 0.000. The findings show a positive relationship between parental involvement and readiness to learn. This suggests that the higher the parental involvement, the higher the children's readiness to learn, and conversely, lower parental involvement results in lower readiness to learn in children.